Displacement rate effects on mixed-mode I/II delamination of laminated carbon/epoxy composites. (April 2022) - Low, Kean Ong; Johar, Mahzan; Sung, Aun Naa; Mohd Nasir, Mohd Nazri; Rahimian Koloor, Seyed Saeid; Petrů, Michal; Israr, Haris Ahmad; Wong, King Jye
Abstract: Mixed-mode delamination is one of the common failures of composites which has not been studied under low-impact loading. This paper studies the influence of displacement rate on mixed-mode I/II delamination of unidirectional carbon/epoxy composites. Single leg bending test is performed at displacement rates of 1, 10, 100, and 500 mm/min. Experimental results reveal that the mixed-mode I/II fracture toughness is invariant with the displacement rate. In addition, scanning electron micrographs shows that shear cusps are more obvious at 1, 10, and 100 mm/min. At 500 mm/min, significant matrix debris is noticed. Furthermore, the proposed three-dimensional rate-dependent fracture criterion is found to well predict the fracture toughness. Numerical simulation using cohesive zone model suggests that the lower numerical peak load is due to lower damage dissipated energy. In addition, the theoretical and numerical traction-separation responses show significant differences, which is also reflected in the numerical phase angle. This implies that the local mixed-mode ratio is not constant throughout the simulation process. Highlights: Interlaminar damage behavior of carbon/epoxy composite laminates Development of a three-dimensional rate-dependent fracture criterion to predict the fracture toughness Investigation on the mixed-mode I/II delamination using single-leg bending test Study the effect of displacement rate (1, 10, 100, and 500 mm/min) on mixed-mode I/II delamination Fractographic analysis of mixed-mode I/II interface fracture Three-dimensional simulation of interface fracture and examination of the theoretical aspect of the interface damage mechanics.